"Lest we forget": An overview of Australia's response to the recovery and identification of unrecovered historic military remains. (November 2021) - MacGregor, Donna M.; Lain, Russell; Bernie, Andrew; Cooper, Alan; Dawe, Tim; Donlon, Denise; Fitzmaurice, Terrence; Kelly, Grant; Heiman, Scott; Lowe, Anthony; Manns, Brian; Matic, Ashley; et al.
Abstract: The Australian Defence Force (ADF) is responsible for the recovery and identification of its historic casualties. With over 30, 000 still unrecovered from past conflicts including World War One (WW1) and World War Two (WWII), the Australian Army and Royal Australian Air Force have teams that research, recover, identify and oversee the burial (or reburial) of the remains of soldiers and airmen who continue to be found each year. The Royal Australian Navy is also responsible for its unrecovered casualties. Collectively the priorities of the various services within the ADF are the respectful recovery and treatment of the dead, thorough forensic identification efforts, resolution for families and honouring the ADF's proud history of service and sacrifice. What is unique about the approach of the ADF is that the respective services retain responsibility for their historic losses, while a joint approach is taken on policies and in the utilisation of the pool of forensic specialists. Section One describes the process undertaken by the Australian Army in the recovery, identification and burial or repatriation of soldiers through its specialised unit Unrecovered War Casualties - Army (UWC-A). Section Two describes the role of the Royal Australian Air Force in the recovery of aircraft and service personnel through their specialised unit Historic Unrecovered War Casualties – Air Force (HUWC-AF). An overview of the operations of each service and case studies is presented for each section.